A two-dimensional parabolic model for flood assessment - Prestininzi, Pietro; Fiori, Aldo (Italian journal of engineering geology and environment, 2006)
A two-dimensional numerical model for simulating water flood is presented. The model formulation employs a parabolic approximation for the shallow-water equations. The flow equations are solved by means of a numerical semi-implicit method based on mass balance applied to cells whose elevation is derived directly from topographic data survey described by DEM. Boundary conditions are described as prescribed level-discharge relations. A comparison with a physical imposed model and a real application of an urban area flood are described.